OSCILLATIONS OF A CYLINDRICAL SHELL IN CONTACT WITH A VISCOUS FLUID - Butunov Jakhongir Ruziqulovich; Karimova Sanobar Toyboyevna; Mirzoyeva Gulzira Toraqul qizi (Modern American Journals, 2026)
The paper considers the three-dimensional diffraction of impulsive longitudinal waves by a cylindrical cavity. The cavity is embedded in an unbounded, isotropic, homogeneous elastic medium. It is assumed that a point source of longitudinal waves generating the incident impulse is located outside the cavity. A formal solution to the problem is obtained in integral form. A general algorithm is presented for computing Bessel and Hankel functions with complex arguments, as well as algorithms based on Müller’s method for determining residues and Romberg’s method for evaluating improper integrals. In a cylindrical coordinate system, a dissipative system consisting of a cylindrical body is considered. All systems examined in this work are assumed to be homogeneous and isotropic.
Keywords: Diffraction, longitudinal waves, elastic medium, Müller’s method, cylindrical body.